Sensorimotor Integration in the Whisker System - Krieger, Patrik; Groh, Alexander (Springer New York : Imprint: Springer, 2015)
Sensorimotor integration, the dynamic process by which the sensory and motor systems communicate with each other, is crucial to humans' and animals' ability to explore and react to their environment. This book summarizes the main aspects of our current understanding of sensorimotor integration in 10 chapters written by leading scientists in this active and ever-growing field. This volume focuses on the whisker system, which is an exquisite model to experimentally approach sensorimotor integration in the mammalian brain. In this book, authors examine the whisker system on many different levels, ranging from the building blocks and neuronal circuits to sensorimotor behavior. Neuronal coding strategies, comparative analysis as well as robotics illustrate the multiple facets of this research and its broad impact on fundamental questions about the neurobiology of the mammalian brain.